ACCOUNTING CONSERVATISM, CORPORATE GOVERNANCE, AND MANAGERIAL OWNERSHIP IN TAX AVOIDANCE PRACTICES - Dian Ayu Lestari; Intan Kurnia Permatasari (Universitas KH. Abdul Chalim Mojokerto, 2026)
Tax avoidance remains a persistent issue due to its potential to undermine the effective maximization of public revenue. This study dives into the issue by exploring how cautious accounting practices, the oversight role of audit committees, and the share of independent commissioners connect to tax avoidance, with managerial ownership thrown in as a factor that might tweak these relationships. The research zeroes in on mining companies listed on the Indonesia Stock Exchange from 2020 to 2024, compiling 208 data points for analysis. To test the hypotheses, both multiple linear regression and moderated regression analysis (MRA) were applied. The results show that conservative accounting and active audit committees are linked to lower levels of tax avoidance. Meanwhile, the role of independent commissioners does not exhibit a statistically meaningful relationship. Additionally, managerial ownership is not evidenced to significantly alter the strength or direction of the relationships between the studied variables and tax avoidance.